2018
DOI: 10.4103/ams.ams_154_17
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytoma parotid gland

Abstract: Very few cases of parotid oncocytoma have been reported in literature. Because of its rarity (<1% of salivary gland tumors) and clinical presentation of the tumor, there is a tendency among the clinicians to misdiagnose it as pleomorphic adenoma, hemangioma, or other forms of oncocytosis. Only a histopathological examination can confirm it. We evaluate here a case of swelling of the parotid gland in a 70-year-old male who had the tumor for over 9 years to reach a diagnosis. Furthermore, our aim is to bring to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Based on the studies of Capone and Shellenberger et al, more than one oncocytic variant can exist in a single parotid gland, lending credibility to the possibility of a common mitochondrial defect that promotes a step-by-step advancement through the variants [8], [11]. Other proposed explanations for oncocytic change consider it a metaplastic change or a product of aging [12]. The underlying cause of oncocytomas is yet unknown, but there may be an association with radiation exposure [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the studies of Capone and Shellenberger et al, more than one oncocytic variant can exist in a single parotid gland, lending credibility to the possibility of a common mitochondrial defect that promotes a step-by-step advancement through the variants [8], [11]. Other proposed explanations for oncocytic change consider it a metaplastic change or a product of aging [12]. The underlying cause of oncocytomas is yet unknown, but there may be an association with radiation exposure [9].…”
Section: Discussionmentioning
confidence: 99%
“…These tumors typically affect individuals between their sixth to eighth decade. Although there is no strong sex predilection, it is reported that women in their seventh or eighth decade may be more commonly affected [1], [2], [3]. A history of radiation exposure 5 or more years prior to presentation has been noted in 20% of cases [4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the oncocytoma, these lesions do not present as solitary delineable mass but as lesion consisting of multiple oncocytic nodules. Often they are diagnosed accidentally and there is no tendency regarding malignant degeneration 149 150 .…”
Section: Rare Diseases Of the Salivary Glandsmentioning
confidence: 99%
“…Im Gegensatz zum Onkozytom präsentiert sich diese Läsion nicht als solitär abgrenzbare Raumforderung, sondern als Läsion bestehend aus multiplen onkozytären Knötchen. Sie ist oft nur ein Zufallsbefund und es besteht keine Tendenz zur malignen Entartung 149 150 .…”
Section: 613 Onkozytome Und Noduläre Hyperplasienunclassified
“…Although the parotid is the gland with the highest incidence (84% of the cases), some cases have been reported involving the submandibular or sublingual glands [ 20 ] The encapsulated painless mass grows slowly and it is composed quite exclusively of oncocytes. Oncocytes are polyhedral epithelial cells, double the size of normal acinar cells, characterized by a condensed round nucleus and a mitochondria-rich cytoplasm that is positive for phosphotungstic acid–hematoxylin (PTAH) staining ( Figure 1 b) [ 21 ]. Secretory epithelia exposed to metabolic stress might evolve into oncocytes to compensate new energetic needs [ 22 ].…”
Section: Benign Tumorsmentioning
confidence: 99%